Digital Transformation as a Strategy for Entrepreneurial Resilience in the Era of a Sustainable Economy: A Case Study of MSMEs in Putri Hijau Sub-district, North Bengkulu Regency - Diki Heryanto; Ahmad Soleh; Karona Cahya Susena (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi, 2026)
Digital transformation has become a key factor in strengthening entrepreneurial resilience amid the increasingly complex dynamics of the global economy. This study aims to analyze the role of digital transformation as a strategic approach to building entrepreneurial resilience toward a sustainable economy, focusing on UMKM in Putri Hijau Subdistrict, North Bengkulu Regency. Using a descriptive-qualitative approach and literature review, the research highlights how business process digitalization, financial technology adoption, and data-driven innovation enhance efficiency, adaptability, and competitiveness among entrepreneurs. The findings indicate that adopting digital technologies not only drives business growth but also reinforces entrepreneurs’ capacity to navigate economic uncertainty and global crises. Therefore, digital transformation can be considered a fundamental strategy for creating a resilient, inclusive, and sustainable entrepreneurial ecosystem at the local level.